QUALITY OF LIFE IN CHILDREN AND ADOLESCENTS WITH DIABETES MELLITUS TYPE 1 - E.V. Kolbasina; V.A. Vorob'eva; E.A. Azova; V.F. Rassokhin ("Paediatrician" Publishers LLC, 2009)
The increase of morbidity with diabetes mellitus (DM) in children and adolescents during last years, and absence of adequate control of disease reveal the need of complex study of quality of life in these patients. The article presents the results of evaluation of quality of life rates, obtained with Russian versions of questionnaires PedsQL 4.0 Generic Core Scale and Diabetic Module in children and adolescents with diabetes type I, treated with different combinations of insulin drugs. The results showed that quality of life differs between group of healthy adolescents and patients with DM. There was correlative dependence between the level of glycated hemoglobin and parameter «school function» of quality of life. Administration of insulin analogs improves some indices of adolescents' with DM quality of life. Estimation of it is one of the main criteria of treatment effectiveness.Key words: children, adolescents, insulin, diabetes type 1, quality of life.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(5):14-18)